UPAYA GURU MENGIMPLEMENTASIKAN MANAJEMEN KELAS TERHADAP PEMBENTUKAN SIKAP DISIPLIN SISWA MELALUI PERATURAN DAN PROSEDUR - Wiputra Cendana; Adelia Juanita (STKIP Subang, 2022)
Based on the results of observations in the 4th grade of Christian Elementary School in Tangerang. Undisciplined attitude was found in students, because class management was not optimal. As a result, the learning process is less effective and conducive. Thus, the importance of maximizing classroom management through the application of rules and procedures as an effort to form students' disciplined attitudes. The purpose of this paper is to discuss the teacher's role in implementing classroom management through rules and procedures, as an effort to form a disciplined attitude for 4th grade students. The method used is descriptive qualitative. From the results of the discussion, it is stated that classroom management through the application of rules and procedures is maximally able to overcome students' undisciplined attitudes. The teacher as a guide is required to be able to direct students to keep walking in the right corridor. Thus, the discipline that is built in students forms a good behavior. In conclusion, class management is said to be successful if the learning objectives are achieved and the students' discipline is formed in stages that are agreed upon and carried out together. Suggestions in the future, teachers need to emphasize and remind the rules and procedures both at the beginning and at the end of learning. Teachers also need to approach students who are not yet disciplined. And, consistently reminding the procedures that apply continuously, so that they hope to form positive habits that students carry throughout their lives.